Remarkable Protective Effects of Nrf2-Mediated Antioxidant Enzymes and Tissue Specificity in Different Skeletal Muscles of Daurian Ground Squirrels Over the Torpor-Arousal Cycle - Wei, Yanhong; Zhang, Jie; Yan, Xia; Peng, Xin; Xu, Shenhui; Chang, Hui; Wang, Huiping; Gao, Yunfang (Frontiers in Physiology, 2019)
Hibernating mammals experience extreme oxidative stress conditions, such as fasting, muscle disuse, and repeated hypoxic ischemia-reperfusion, during the torpor-arousal cycle. Despite this, they experience little oxidative injury and are thus an interesting model of anti-oxidative damage. The Nrf2/Keap1 signaling pathway are significant for antioxidant defense. Thus, in the current study, we explored the levels and underlying mechanism of oxidative stress and antioxidant capacity in three skeletal muscles (slow-twitch soleus (SOL), fast-twitch extensor digitorum longus (EDL), and mixed gastrocnemius (GAS)) during the entire hibernation period in Daurian ground squirrels (Spermophilus dauricus). Results showed that hydrogen peroxide content in the EDL and GAS decreased significantly during pre-hibernation (PRE) and late torpor (LT) compared to levels in the summer active (SA) group. Furthermore, relative to SA levels, malondialdehyde content decreased significantly during interbout arousal (IBA) and early torpor (ET) in all three skeletal muscles and decreased in the EDL and GAS muscle during LT. Compared with the SA group, glutathione peroxidase 1 (GPx1) and catalase (CAT) protein expression in the SOL and superoxide dismutase 1 (SOD1) and SOD2 expression in the GAS were significantly increased during the entire hibernation season. In the EDL, SOD1 in the IBA group and CAT and GPx1 in the ET and LT groups increased significantly. In addition, the activities of most tested antioxidant enzymes were higher in the IBA group than in the LT group, whereas CAT remained highly active throughout the hibernation season in all three muscles. Nrf2 and p-Nrf2 protein levels in the SOL and EDL were significantly elevated during hibernation, and increased during the PRE, IBA, and ET states in the GAS. These results indicated that activation of the Nrf2/Keap1 antioxidant pathway can eliminate excess reactive oxygen species and maintain physiological levels by up-regulating antioxidant enzyme expression in skeletal muscle under multiple oxidative stress conditions during hibernation, thereby preventing squirrels against oxidative injury over the torpor-arousal cycle. Under hibernation conditions, with physiological suppression of certain functions, the expression of antioxidant enzymes was up-regulated, suggesting that enhancement of antioxidant defense is crucial for coping with the high stress environments of successful hibernation in Daurian ground squirrels.